Association Between Peripheral Inflammation and DATSCAN Data of the Striatal Nuclei in Different Motor Subtypes of Parkinson Disease - Sanjari Moghaddam, Hossein; Ghazi Sherbaf, Farzaneh; Mojtahed Zadeh, Mahtab; Ashraf-Ganjouei, Amir; Aarabi, Mohammad Hadi (Frontiers in Neurology, 2018)
The interplay between peripheral and central inflammation has a significant role in dopaminergic neural death in nigrostriatal pathway, although no direct assessment of inflammation has been performed in relation to the dopaminergic neuronal loss in striatal nuclei. In this study, the correlation of neutrophil to lymphocyte ratio (NLR) as a marker of peripheral inflammation to striatal binding ratios (SBR) of DAT-SPECT images in bilateral caudate and putamen nuclei were calculated in 388 drug-naïve early PD patients (288 tremor-dominant, 73 postural instability and gait difficulty (PIGD), and 27 intermediate) and 148 controls. NLR was significantly higher in PD patients than age and sex-matched healthy controls. NLR showed a negative correlation to SBR in the bilateral putamen in all PD subjects. Among our three subgroups, only TD subgroup showed remarkable results. A positive association between NLR and motor severity was observed in TD subgroup. Besides, NLR could negatively predict the SBR in ipsilateral and contralateral putamen and caudate nuclei in tremulous phenotype. Nonetheless, we found no significant association between NLR and other clinical and imaging findings in PIGD and intermediate subgroups, supporting the presence of distinct underlying pathologic mechanisms between tremor and non-tremor predominant PD at early stages of the disease.